Assessments for Caregivers of Hospitalized Older Adults. (July 2020) - Fields, Beth; Turner, Rose L.; Naidu, Maharsi; Schulz, Richard; James, Everette; Rodakowski, Juleen
A systematic review was conducted to characterize assessments for caregivers of hospitalized older adults. Electronic literature searches of Medline, PsycINFO, and CINAHL of articles on caregiver assessments published in English between 2006 and present were completed. Thirty-three articles underwent full-text review; four included assessments designed to capture caregiver needs in hospital settings. Original articles on the development of these assessments were reviewed for quality appraisal. Four findings emerged from our review. Existing assessments (a) focus on caregivers of specific conditions of older adults, (b) contain a singular caregiving domain, (c) measure caregiver outcomes or simply describe caregiving experiences, and (d) neglect psychometric properties. Health care providers are limited in their selection of assessments with caregivers of hospitalized older adults. This barrier is problematic if we are to equip caregivers to be successful at providing care to older adults. Future research should develop a hospital assessment for caregivers.